OPTIMIZATION OF HUMAN RESOURCES QUALITY IN IMPROVING THE PERFORMANCE OF ISLAMIC BANKING EMPLOYEES - Estelee Elora Akbar; Heni Noviarita; Erike Anggraeni (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2020)
The purpose of this study was to find and review the optimization of human resourcesquality in improving the performance of Islamic banking employees. The approach used in this study was a quantitative approach by using primary data obtained through questionnaires to the Islamic banking customers located in Lampung. Sampling technique used in this studywas purposive sampling with a sample size of 100 people. Analysis of the data used in this study was simple linear regression analysis. Based on the result, the study found that there are significant quality of human resources in improving the performance of Islamic banking at 10.3%. Therefore,it needs to do the optimization of human resources quality through various efforts such as the recruitment system, the planning and training given by the company toward the employees, improving the intelligence, creativity, perseverance, as well as the professionalism of the employees.